Versatile Organic Chemistry on Vanadium‐Based Multi‐Electron Reservoirs. Issue 11 (6th February 2018) - Nachtigall, Olaf; Spandl, Johann
Abstract: We report the synthesis, post‐functionalization, and redox behavior of two organically functionalized aggregates, [V6 O7 (OMe)9 (OCH2 )3 C−CH2 N3 ] and [V6 O7 (OMe)9 (OCH2 )3 C−NH2 ]. All twelve μ 2 ‐oxo groups on the edges of the Lindqvist‐type V6 O19 core were replaced by alkoxo ligands. The absence of a negative charge and the closed organic shell make these neutral mixed‐valence compounds very stable towards hydrolysis and well soluble in almost all common organic solvents. These are important advantages over classical POMs. By post‐functionalization through copper(I)‐catalyzed Huisgen cycloaddition or imine formation, various organic moieties could be introduced. Even a well‐soluble trimer composed of three hexanuclear vanadium units connected through an aromatic triimino core was synthesized and studied. The diverse redox behavior, the versatile reactivity, the good stability, and the excellent solubility make our vanadium compounds highly interesting for applications as building blocks in macromolecular chemistry as well as redox labels in biochemistry. Abstract : Reservoir POMs : Strategies are provided for the organic functionalization and post‐functionalization of neutral Lindqvist‐type vanadium alkoxides with high solubility and redox activity. The functionalized aggregates can be applied as building blocks in macromolecular chemistry, multi‐electron reservoirs in functional materials, or redox labels in biochemistry.